체언 끝의 변화 ‘ㄷ, ㅈ, ㅊ, ㅌ＞ㅅ’에 대한 재론 - 고광모(Kwang-mo Ko) (언어학, 2014)
This paper deals with the noun stem-final change t, c, ch, th＞s in Westerndialects of Korean. This change affected the noun stem-final coronal obstruentsbefore vowel-initial suffixes: for example, kat-i＞kas-i ‘Korean hat＋nominativesuffix’, pich-ul＞pis-ul ‘light＋accusative suffix’. The change began to occur inthe 17th century and has not been completed yet. Why and how the changetook place can be explained as below. 17th century Korean had t, s, c, ch and th for noun stem-final coronalobstruents. They were realized before vowel-initial suffixes as [d, s, j, cʰ, tʰ]respectively. But in unsuffixed isolation forms and before consonant-initialsuffixes they were neutralized to [t]. This neutralization resulted fromdiachronic changes. In the 17th century [s] was by far most frequently realizedsound among the noun stem-final coronal obstruents. And speakers recognizedthe isolation forms as underlying in spite of the fact that relative tokenfrequency of the isolation forms (plus forms before consonant-initial suffixes)was lower than that of the forms before vowel-initial suffixes. This can beexplained by the following fact. When we bring to mind a noun, it is alwaysthe isolation form that occurs to us. The rules that applied prevocalically to nouns ending in a coronal obstruentwere /t/→[d], /t/→[s], /t/→[j], /t/→[cʰ] and /t/→[tʰ]. These rules could not bepredicted and speakers had to remember which rule applied to each noun. Thelatter four of the above rules are inverted rules because the directions of themare opposite respectively to those of the diachronic changes s＞t, c＞t, ch＞tand th＞t that occurred in coda position. The rule /t/→[s], which applied byfar most frequently, has begun to replace the other rules. This replacement is the noun stem-final change t, c, ch, th＞s. By this change t-, c-, ch- and th-finalstems become s-final and the t～s alternation is extended. This is an exampleof analogical extension. The replacement of the rule /t/→[d] with the rule /t/→[s] occurred first andhas already been completed. The fact that the t([d])-final stem is least resistentto the change can be explained as follows. Since the 16th century Korean hasthe t～s alternation but no alternations such as c～s, ch～s and th～s. The t～salternation has greatly high frequency, therefore there is a close relationshipbetween t([t/d]) and s and speakers may be somewhat insensitive to differencebetween them. On the other hand, ch([cʰ])- and th([tʰ])-final stems are quiteresistant to the change. This is most probably because perceptual salience of[cʰ] and [tʰ] attracts speakers' keen attention. Nouns of place and time arespecial. Their locative forms, i.e., their stems plus the locative suffix -ey havebeen nearly fused into single units. Therefore their stems before the locativesuffix are most strongly resistant to the change. KCI Citation Count: 6